Research success : a Q & A review applying critical thinking to test taking 2026-02-15T19:26:06+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Valencia Go, Geraldine N. (Davis's Q & A success series, 2016)

(untitled)
"From an introduction to basic research concepts through design of quantitative and qualitative studies and data collection and analysis, you'll review all aspects of nursing research and its application to real-world practice. More than 700 NCLEX-style questions (including alternate format) in the text at Davis:Plus offer test-taking tips and rationales for correct and incorrect answers. Critical thinking facilitators for every item and research study question support learning and enhance critical thinking"--